Patronase Dalam Kuasa Kepala Desa Perempuan Desa Besuki Kabupaten Blitar - Dhaehasti Agustina Saputri (Fakultas Ilmu Sosial Dan Ilmu Politik Universitas Jember, 2025)
Besuki Village, located in Udanawu Subdistrict, Blitar Regency, has experienced significant changes in agricultural access and government–community coordination, particularly with women through the PKK, since the leadership of Mrs. Hanik. She is the first female village head of Besuki Village and has successfully secured two consecutive terms in office by building trust and sustaining community loyalty. This study analyzes the patronage practices exercised by the female village head of Besuki Village, Blitar Regency, in maintaining her political power. The research applies Edward Aspinall and Ward Berenschot’s theory of patronage and clientelism, which highlights three key concepts: networks, control patterns, and resources. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation with purposively selected informants. Data analysis involved organizing, reducing, and presenting data, followed by drawing conclusions. The validity of findings was strengthened through methodological and theoretical triangulation. Findings indicate that Mrs. Hanik developed relationships through religious networks and village institutions, initially forming bonding networks. Over time, these networks became more institutionalized, acting as intermediaries and channels of two-way communication between the village head and the community, functioning as brokers. Through these networks, Mrs. Hanik controlled resources and strengthened loyalty. Resources, such as collective goods and gifts, contributed to a positive public image, which was instrumental in maintaining loyalty. Institutionalized networks proved effective in ensuring resource distribution efficiency, particularly through structured access to women’s empowerment and agricultural programs. This sustained positive image fostered continuous community loyalty, which became the foundation of Mrs. Hanik’s political success and her ability to secure two consecutive terms.
Reuploud file repositori 15 Apr 2026_Firli_Tata
Keywords: female village head; patronage; loyalty